Long‐term efficacy and safety of eslicarbazepine acetate monotherapy for adults with newly diagnosed focal epilepsy: An open‐label extension study - Trinka, Eugen (Epilepsia, 2020)
OBJECTIVE: To assess the efficacy, safety, and tolerability of eslicarbazepine acetate (ESL) monotherapy during long‐term treatment. METHODS: An open‐label extension (OLE) study was conducted in adults completing a phase 3, randomized, double‐blind, noninferiority trial, during which they had received monotherapy with either once‐daily ESL or twice‐daily controlled‐release carbamazepine (CBZ‐CR) for newly diagnosed focal epilepsy. In the OLE study, all patients received ESL (800‐1600 mg/d) for 2 years. Primary efficacy outcome was retention time (from baseline of the OLE study). Secondary efficacy assessments included seizure freedom rate (no seizures during the OLE study) and responder rate (≥50% seizure frequency reduction from baseline of double‐blind trial). Safety assessments included evaluation of treatment‐emergent adverse events (TEAEs). RESULTS: Of 206 randomized patients, 96 who received ESL in the double‐blind trial (ESL/ESL) and 88 who received CBZ‐CR in the double‐blind trial (CBZ‐CR/ESL) were treated with ESL monotherapy (89.3% overall). Treatment retention time was similar between groups, with low probability of ESL withdrawal overall (<0.07 at any time). After 24 months, the probability of ESL withdrawal was 0.0638 (95% confidence interval [CI] = 0.0292‐0.1366) in the ESL/ESL group and 0.0472 (95% CI = 0.0180‐0.1210) in the CBZ‐CR/ESL group. Seizure freedom rates were 90.6% (ESL/ESL) and 80.7% (CBZ‐CR/ESL; P = .0531). Responder rates remained >80% in both groups throughout the study. Incidence of serious TEAEs was similar between groups (7.3% vs 5.7%; 0% vs 1.1% possibly related), as were the incidences of TEAEs considered at least possibly related to treatment (17.7% vs 18.2%) and TEAEs leading to discontinuation (3.1% vs 4.5%). The types of TEAEs were generally consistent with the known safety profile of ESL. SIGNIFICANCE: ESL monotherapy was efficacious and generally well tolerated over the long term, including in patients who transitioned from CBZ‐CR monotherapy. No new safety concerns emerged.